Melatonin and other parameters of blood antioxidant system in volleyball players during an annual training cycle - Konarska, A.; Karolkiewicz, J.; Pilaczynska-Szczesniak, L. (Human Movement, 2006)
The aim of the study was to analyze changes in prooxidant-antioxidant balance parameters, with special focus on melatonin as an antioxidant, in volleyball players during an annual training cycle.